Modeling biomass and yield production based on nitrogen accumulation in soybean grown in upland fields converted from paddy fields in Japan - Satoshi Nakano (Taylor & Francis Group, 2021)
Crop models can help in identifying constraints to crop production and enhancing crop yield. Because one of the major constraints is the availability of nitrogen for seed production, evaluation of nitrogen accumulation is important for soybean crop models. In the present study, we developed a soybean crop model to evaluate biomass production and nitrogen accumulation of Japanese soybean cultivars grown in upland fields converted from paddy fields. The model simplified the effects of leaf nitrogen deficit on biomass production by reducing only the leaf area while maintaining leaf nitrogen concentration, and we introduced a zero-order reaction kinetics model to estimate soil nitrogen supply. The proposed model was observed to simulate the accumulation of aboveground biomass and nitrogen content in both nodulating and non-nodulating soybean cultivars until the mid-seed filling period. The model accounts for 94% of the observed variations in aboveground biomass and nitrogen content and for 69% of the observed variation in seed biomass. The normalized root mean square errors of aboveground biomass, nitrogen content, and seed biomass are 19.3%, 19.6%, and 20.2%, respectively. Because the model does not include the effects of soil water status on pod formation and nitrogen fixation, seed biomass was overestimated in some cases. However, our model quantified the effects of changes in the soil nitrogen supply and biological nitrogen fixation on soybean production and will be useful for identifying and eliminating production constraints in Japanese soybeans.